Cascade of care among hepatitis B patients in Maastricht, the Netherlands, 1996 to 2018 - Eva van Oorschot; Özgür M. Koc; Astrid ML. Oude Lashof; Inge HM. van Loo; Robin Ackens; Dirk Posthouwer; Ger H. Koek (Elsevier, 2022)
Background & aims: There are approximately 49,000 people (0.34%) in the Netherlands with a chronic hepatitis B virus (HBV) infection. It is unclear how many are linked to care and under follow-up in hepatitis outpatient clinics. This study determined the cascade of care and identified predictors for not being linked to care and loss to follow-up in Maastricht, the Netherlands. Methods: All hepatitis B surface antigen (HBsAg)-positive patients between December 1, 1996 and September 30, 2018 were retrospectively identified. Results: In total, 644 HBsAg-positive patients were identified; of whom 75 had acute HBV infection, 471 chronic HBV infection and 98 unknown. Out of 569 individuals with a chronic/unknown HBV status, 134/569 (23.6%) were not linked to care and 58.7% (195/332 after excluding those who died or achieved HBsAg-seroclearance) were loss to follow-up (LTFU). A predictor for not being linked to care was Caucasian ethnicity (odds ratio (OR) = 2.76 (95% Confidence Interval (CI) = 1.21-6.29); p = .015). Predictors for LTFU were older age (OR = 0.97 (CI = 0.94-0.99); p = .008), HBV DNA >20,000 IU/mL (OR = 0.44 (CI = 0.21 - 0.93); p = .033) and Asian ethnicity (OR = 0.46, (CI = 0.21-1.00); p = .050). Rates of not being linked to care and LTFU decreased over time from 12.7% in 1996 to 4.4% in 2018 and from 79.2% in 1996 to 37.2% in 2018, respectively. Conclusions: A considerable amount of HBsAg-positive individuals were not linked to care or LTFU. This study indicates that ethnicity plays a role in linkage to care and follow-up. Further research is needed to elaborate on those results.